Improving High School Students' Creative Thinking Skills through Role-Playing Learning Models on Digestive System Material - Siti Nur Annisa Boang Manalu; Syarifah Widya Ulfa (Universitas Labuhanbatu, 2024)
This research This exploration intends to further develop understudies' innovative reasoning abilities through role-playing learning models on the digestive system material at senior high school of SMAN 2 Sidikalang, Dairi Regency. In order to accomplish this goal, A quasi-experimental with a nonequivalent control group was utilized in a quantitative study design. There were 60 subjects in all; The experimental and control group was using 30 person second grade (XI) MIPA on each part. the hypothesis was tested using t-independent data analysis to see how much influence and there was a difference in the students ability for creative thinking between the class that exclusively used the conventional method of learning and other class. The data for this study used an instrument, namely essay questions in the form of pre-test questions (before being treated) and post-test questions (after being treated), to quantify creative thinking skill. The SPSS v26 factual investigation results showed that The experimental class had an average worth of 80.00, whereas the control class had an average worth of 75.00, the T-test was performed to further demonstrate whether the difference was significant, where the Sig value (2-tailed) was 0.027 <0.05. In descriptive statistics, There were differences in the average level of creative thinking among students in the experimental and control groups. The t-test results showed that there was a significant difference between role-playing and simulation learning in terms of enhancing students' capacity for creative thinking skill